Histone variants and modifications during abiotic stress response - Nunez-Vazquez, Rocío; Desvoyes, Bénédicte; Gutierrez, Crisanto (Frontiers in Plant Science, 2022)
Plants have developed multiple mechanisms as an adaptive response to abiotic stresses, such as salinity, drought, heat, cold, and oxidative stress. Understanding these regulatory networks is critical for coping with the negative impact of abiotic stress on crop productivity worldwide and, eventually, for the rational design of strategies to improve plant performance. Plant alterations upon stress are driven by changes in transcriptional regulation, which rely on locus-specific changes in chromatin accessibility. This process encompasses post-translational modifications of histone proteins that alter the DNA-histones binding, the exchange of canonical histones by variants that modify chromatin conformation, and DNA methylation, which has an implication in the silencing and activation of hypervariable genes. Here, we review the current understanding of the role of the major epigenetic modifications during the abiotic stress response and discuss the intricate relationship among them.